Symbolic meanings of ordinary city streets and their trees - Ferguson, Bruce K. (Frontiers in Psychology, 2023)
Symbolic meaning is one of a number of modes of humans’ relationships with physical settings. Although symbolic meaning is qualitative and ambiguous, it is an encompassing mode of interaction: symbolic meanings assemble feelings, urges, and abstract concepts; they shape people’s understanding of the world and motivate their purposes, attitudes, and actions. Early literature in environmental psychology acknowledged symbolic meaning’s promise, but in recent decades it has been inadequately studied; theoretical and methodological research has been needed. This paper advances the understanding and use of symbolic meaning by, first, presenting a theory which posits that in ordinary environmental settings symbolic meanings emerge from interaction between the perceptible qualities of environmental features and people’s psychological predisposition to respond to them. The paper then demonstrates methods which use the theory to objectively guide the identification of symbolic meanings in the case of ordinary urban streets and their trees. Although symbolic interpretation is intuitive and subjective, in this study it is guided by objective empirical knowledge and theoretical frameworks from human sciences. A combination of methods is applied, making conclusions answerable to diverse types of underlying data. One method was in firsthand observation of present-day streets; interpretations were accepted which linked objects’ perceptible qualities with people’s known dispositions to respond to them. A second method was interpretation in conventional street features’ documented historical evolution. Interpretations were accepted which linked objects’ perceptible qualities with people’s known disposition to respond, and with symbols’ known cultural tendency over time to specialize, differentiate, and evolve into coherent systems consistent with social norms. The results confirm that ordinary streets and their trees form a coherent system of symbols. Their meanings are social and sociomoral; they are guides to and affirmations of humane social life; they deserve to be prioritized in design agendas alongside tangible performance measures. It is concluded that symbolic meanings are present in ordinary urban settings, that their presence can be explained theoretically, and that their interpretation can be objectively guided.